A novel ladle for metal industry. (2021) - Chatterjee, Debasish
Abstract: In the present study a novel ladle metallurgy is innovated which will enhance the mixing efficiency of the metallurgical reactor. By applying this technology approximately 41% improvement in mixing time was observed in numerical simulation. The velocity profile and mixing time were compared with normal ladle and this novel ladle. There is a high negative pressure is generated at the plume region for 5 co-centric plugs novel ladle. This cause development of a large swirling flows throughout the ladle fluid. This is not observed for normal ladle purging system. This high rate swirling flows create less mixing time for novel ladle. It is not affected the wear of the ladle so much.